An approach to rheological and electrokinetic behaviour of lipidic vesicles covered with chitosan biopolymer - Madrigal-Carballo, Sergio (2008)
The rheological and electrokinetic properties of soybean lecithin vesicles prepared from concentrated soy lecithin dispersions (250 g/L) obtained by slow swelling under shear conditions and mixed with chitosan biopolymer solutions were studied. The rheological behaviour of lecithin-chitosan vesicles was determined by shear stress against shear rate measurements, as well as by the variation on the hysteresis loop area. The results were compared with the rheopectic behaviour of soy lecithin dispersions without chitosan. An important change on the rheological properties of the complex dispersion was observed, depicting in a thixotropic behaviour with a plastic character in the presence of chitosan. This observation indicates that chitosan promotes the transition of planar sheets into closed structures, such as vesicles. The influence on the rheological and the electrokinetic behaviours of several electrolytes, such as NaCl, CaCl2 and AlCl3 with concentrations ranging between 10-5 and 10-2 mol/L were also studied. In all of the cases, an estimation of the diameters of the closed structures was obtained. © 2007 Elsevier B.V. All rights reserved.